143k views
0 votes
Solve the equation. 4(x − 7) − 128 = 9x − 5(x + 6)

User Yassar
by
6.5k points

1 Answer

4 votes

The equation 4(x − 7) − 128 = 9x − 5(x + 6) has no solution

Solution:

Given that 4(x − 7) − 128 = 9x − 5(x + 6)

We have to find the solution for this equation

4(x − 7) − 128 = 9x − 5(x + 6)

Let us use BODMAS rule to perform the sequence of operations

According to Bodmas rule, if an expression contains brackets ((), {}, []) we have to first solve or simplify the bracket followed by of (powers and roots etc.), then division, multiplication, addition and subtraction from left to right.

So let us solve for brackets first

4x - 28 - 128 = 9x - 5x - 30

Now let us perform subtraction

4x - 156 = 4x - 30

Now move the terms from R.H.S to L.H.S

4x - 4x = -30 + 156


0 \\eq 126

Since there is no value of x that will ever make this a true statement, the solution to the equation above is “no solution”

So this equation has no solution

User Nitrl
by
5.6k points